IDENTIFIKASI KESADARAN DIRI PADA SISWA DI SMKN 9 MUARO JAMBI - Tiara Haliza; Muhammad Ferdiansyah; Rully Andi Yaksa (STKIP Subang, 2026)
Student self-awareness in school is a psychological condition that often occurs, related to an individual's ability to recognize, understand, and manage emotions while adapting to demands and the environment effectively. This study aims to identify aspects of self-awareness of students at SMKN 9 Muaro Jambi. This study uses a descriptive quantitative approach with a sample of 204 students selected through a simple random sampling technique. Data were collected using a Likert scale questionnaire whose validity and reliability have been tested using SPSS 26. The results show that self-awareness of SMKN 9 Muaro Jambi students is in the good category (67%), with details that self- assessment is (70%), recognizing emotions (69%), and self-confidence (62%). This illustrates that most students have quite good abilities in understanding themselves and their emotions, but still need to strengthen their self-confidence. This study is expected to provide more in-depth insights for guidance and counseling teachers who need to design and implement programs that focus on developing student self-awareness, namely recognizing emotions, self-assessment, and self-confidence, as well as providing a basis for schools and parents in decision-making and student resilience against negative influences from the surrounding environment. Keywords: Self Awarness, Emotions, Self-Assesment, Self-Confidence